2015
DOI: 10.3174/ajnr.a4483
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility Vessel Sign on MRI Predicts Favorable Clinical Outcome in Patients with Anterior Circulation Acute Stroke Treated with Mechanical Thrombectomy

Abstract: BACKGROUND AND PURPOSE:The susceptibility vessel sign on MR imaging has been reported to indicate acute occlusion from erythrocyte-rich thrombus. The purpose of this study was to evaluate the influence of the susceptibility vessel sign seen on MR imaging before treatment on the clinical outcome after mechanical thrombectomy for anterior circulation acute stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 35 publications
5
32
1
Order By: Relevance
“…Our findings are in line with a previous smaller retrospective monocentric study, in which SVS+ appeared to be a radiologic biomarker predictive of favorable clinical outcome at 3 months after MT 10. However, a very large CI precluded any generalization of the results (OR=8.7; 95% CI 1.1 to 69.4; P value 0.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings are in line with a previous smaller retrospective monocentric study, in which SVS+ appeared to be a radiologic biomarker predictive of favorable clinical outcome at 3 months after MT 10. However, a very large CI precluded any generalization of the results (OR=8.7; 95% CI 1.1 to 69.4; P value 0.…”
Section: Discussionsupporting
confidence: 90%
“…A recent study showed that the presence of an SVS predicted favorable clinical outcomes in patients with anterior circulation strokes who underwent endovascular treatment. 16 However, SVS was not significantly associated with successful recanalization (81% versus 70% of TICI ≥2b in the SVS-positive and SVS-negative groups, respectively; P =0.34). Soize et al showed that the longer thrombi were associated with poor recanalization using a stent retriever.…”
Section: Discussionmentioning
confidence: 83%
“…Whatever the origin of the thrombus, in acute ischaemic stroke, the susceptibility vessel sign would be correlated with:a lower rate of recanalisation after intravenous thrombolysis compared with arterial occlusion without the susceptibility vessel sign [10, 11], particularly for proximal localisations [12], for lengths greater than 20 mm, for thrombi with irregular contours [13], and for susceptibility artefacts extending beyond the arterial lumen [14];a favourable 3-month functional outcome in patients who undergo mechanical thrombectomy for anterior circulation occlusion [15], but not with a higher rate of recanalisation [16]. …”
Section: Swi Sequencesmentioning
confidence: 99%
“…a favourable 3-month functional outcome in patients who undergo mechanical thrombectomy for anterior circulation occlusion [15], but not with a higher rate of recanalisation [16]. …”
Section: Swi Sequencesmentioning
confidence: 99%